Karakterisasi Dan Identifikasi Molekuler Fusan Hasil Fusi Protoplas Interspesies Chlorella pyrenoidosa dan Chlorella vulgaris Menggunakan 18SrDNA - Rismiarti, Asih; Kusumaningrum, Hermin Pancasakti; Zainuri, Muhammad (Bioma : Berkala Ilmiah Biologi, 2016)
Chlorella pyrenoidosa is a unicellular green algae that grows in fresh water with carotenoids consisting of             β-carotene, α-carotene, anthaxanthin, neoxanthin, zeaxanthin and lutein. C. vulgaris usually it lives in sea water with carotenoids, chlorophyll, tocopherol, ubiquinone and proteins. The quality of them is improved by protoplast fusion and identified further using moleculer analysis. This study aims to find out the characterization and identification of molecular fusan that is obtained from interspecies C. pyrenoidosa and C. vulgaris protoplast fusion process using 18SrDNA. Both C. pyrenoidosa and C. vulgaris are combined by protoplast fusion and then they were performed the isolation of DNA with CTAB modification method, followed by PCR gradient using primers 18S Chlorella and performed DNA sequencing. The result show that there are different characters between masterplan and fusan based on growth of fresh water and sea water medium. The success frequency of fusan as a result from protoplast fusion in the fresh water media is 21% and 6% for sea water medium. The results of the alignment between fresh water fusan and C. vulgaris masterplan from GeneBank shows that the base sequence homology is 93% C. pyrenoidosa masterplan from GeneBank is 90%. The result of molecular identification towards the sequence of fresh water fusan bases shows that there is a kinship relationship with the masterplan of C. pyrenoidosa 18S Chlorella and Chlorosphaera klebsii microalgae compared with some other species from Chlorophyta group with similarity value as many as 91%. It shows that the high variety genetic is based on variations of the base sequence and has a kinship with other species in the Chlorophyta group.                                      Keywords : Chlorella pyrenoidosa, Chlorella vulgaris, Protoplast Fusion, DNA Sequensing, 18SrDNA.